2014
DOI: 10.1097/mca.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of anaemia on patients with ST-elevation myocardial infarction treated by primary PCI

Abstract: Patients with anaemia undergoing PPCI are at a higher risk of an adverse outcome. Anaemia is a simple and powerful marker of poor prognosis. Although anaemia (based on the WHO definitions) does not appear to be an independent predictor of all-cause mortality or major adverse cardiac events after PPCI on multivariate analysis, there appears to be a threshold value of Hb among men, below which there is an associated increased risk for PPCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 2 publications
4
29
1
Order By: Relevance
“…In contrast, other studies suggest that whilst these relationships exists for unadjusted data, anaemia is no longer associated with increased mortality following adjustment for potential confounders such as age, comorbidity burden and procedural demographics, (16,(21)(22)(23), MACE (11,23)or ischemic complications (2). Other studies have also suggested an independent association with mortality only in males but not females (1).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, other studies suggest that whilst these relationships exists for unadjusted data, anaemia is no longer associated with increased mortality following adjustment for potential confounders such as age, comorbidity burden and procedural demographics, (16,(21)(22)(23), MACE (11,23)or ischemic complications (2). Other studies have also suggested an independent association with mortality only in males but not females (1).…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have reported conflicting data regarding the association between anaemia and clinical outcomes in patients undergoing PCI, with studies reporting both an independent association with increased mortality, MACE and major bleeding complications (3,5,(8)(9)(10)(15)(16)(17) or no increase in risk following adjustment for differences in age, comorbidity burden and procedural demographics (9,21,22), or only associated with poorer outcomes in patients with severe anaemia but not mild or moderate anaemia (11). Other studies have suggested that post-procedural anaemia is independently associated with MACE (23).…”
Section: Discussionmentioning
confidence: 99%
“…Much fewer 23 studies have been conducted in patients treated in Intensive 24 Cardiac Care Unit (ICCU). The heterogeneous group of ICCU 25 patients as well as nonspecific complaints associated with anemia 26 might be the reason for underdiagnosing or minimization of this 27 problem. Because of this heterogeneity, there are no clear 28 guidelines to follow.…”
mentioning
confidence: 97%
“…However, there are studies with conflicting 263 outcomes. Rathod et al [27] in their retrospective analysis on a 264 large STEMI population with a mean follow-up period of 3 years 265 mentioned no significant correlation between anemia and long-266 term mortality or major adverse cardiac events. When stratified by 267 g/dL they found an increased risk for adverse outcomes only among 268 men with low Hb levels.…”
mentioning
confidence: 98%
“…Rathoda et al examined 2,178 subjects, of which 419 (19%) were anemic and 1,759 (81%) had normal Hb levels. 16 They reported that anemia (hemoglobin level <13 g/dl) is highly predictive for a poor outcome after primary PCI in comparison with patients with normal serum hemoglobin.…”
Section: Risk Of Invasive Investigations and Treatments In Patients Wmentioning
confidence: 99%